Expression and survival : an aesthetic approach to the problem of suicide - Greenman, Craig (Cambridge Scholars, 2008)
Philosophers know suicide primarily as an ethical problem. But in Expression and Survival, Greenman, Craig argues that, when it comes to suicide, the standard ethical approach may do more harm than good. He develops instead an aesthetic approach, arguing.